Exchange-dependent spin polarized transport and phase transition in a triple monomer molecule. Issue 21 (16th May 2019) - Xiong, Yongchen; Luo, Shijun; Huang, Haiming; Ma, Yanan; Zhang, Xiong
Abstract : Exchange-dependent multi-functional molecular spintronics device based on a triple monomer molecule. Abstract : Molecular junctions contribute significantly to the fundamental understanding of the quantum information technologies in molecular spintronics. In this paper, with the aid of the state of the art numerical renormalization group method, we find a triple monomer molecule structure with strong electron–electron interactions could be a potential candidate for a multifunctional spin polarizer when an external magnetic field along the z axis is applied. It is demonstrated that the polarizing scenarios depend closely on the inter-orbital exchange couplings, and results in several kinds of spin polarizers, e.g., the unidirectional, the bidirectional, the dual, and the ternary spin polarizers. We show in detail the related phase diagram, and conclude the Zeeman effect and the charge switching for the bonding, anti-bonding and non-bonding orbitals are responsible for the spin polarizing transport. We stress even when the energy levels are chosen beyond the Kondo regime, the structure still shows a promising platform for molecular spintronics components.